Strategic Institutional Reform in Islamic Higher Education: The Case of Two Pesantren-Based Universities - Huda, Muhammad Nuril; Supratno, Haris; Hariyati, Nunuk (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
Institutional transformation within pesantren-based Islamic higher education institutions has Institutional transformation within pesantren-based Islamic higher education institutions has become an increasingly significant phenomenon, especially as these institutions seek to strengthen their position amid global competition. There are three purposes of the study: (1) the driving factors behind organizational change in pesantren-based Islamic universities, (2) the processes through which institutional transformation is implemented, and (3) the implications of these changes for institutional development. Employing a qualitative multi-case study approach, the research was conducted at Universitas Hasyim Asy’ari (UNHASY) in Jombang and Universitas Nurul Jadid (UNUJA) in Probolinggo. Methodologically, data were collected through in-depth interviews, participant observation, and document analysis. The results indicate that institutional change is driven by three main factors: the pressure of global competition and market demands, the need to reinforce Islamic and pesantren-based values, and efforts to improve organizational effectiveness and efficiency. The transformation process is implemented incrementally through internal mergers between institutions under a single foundation. This research contributes to enhanced service quality and increased institutional competitiveness by drawing lessons from organizational changes that led to the restructuring of institutional governance in pesantren-based universities.